Pengaruh Game Online terhadap Pemerolehan Bahasa Anak Sekolah Dasar - Muhammad Luqman Asy'ary; Setia Rini; Erna Risfaula Kusumawati (FONDATIA, 2023)
The development of information technology is very fast, many benefits are obtained from the development of this technology. One of the benefits of technological developments is the existence of online Game entertainment facilities. This online Game can have an impact on the language acquisition of elementary school children. This study aims to describe the acquisition of language in grade 4 elementary school children aged 9-11 through semantic studies, namely the study of the meaning of a verb, adjective, or noun. The data source comes from the subject to be studied. This research method uses a qualitative approach. Data collection was carried out using five methods, namely observation, observation, notes, interviews, and questionnaires. The results of this study are that online Games can affect the language acquisition of children aged 9-11 years at SDIT Ibnu Mas'ud, Ambarawa District, marked by an increasingly widespread acquisition of words that are absorbed through online Games, such as verbs (victory, booyah, defeat, login, kill, mabar, drift, survival, by one, ngemoti, push), adjectives (perfect, hockey, noob, idiot, bot, asu, op, good at) and nouns (skin, turret, inventory, tournament) which they apply in everyday language